Estimating and Restricting Growth Rates and Cointegration Means With Applications to Consumption and Money Demand - Håvard Hungnes (Statistics Norway, Research Department, 2001)
The parameters in the cointegration vector and the loading parameters are not the only interesting parameters in a vector cointegration model. With a reformulation of the model the intercept parameters can be decomposed into growth parameters and cointegration mean parameters. These parameters have economic interpretations and are therefore also important. We show how these parameters can be estimated and restricted. The latter can be achieved by using a linear switching algorithm. Consumption and money demand applications illustrate the method.
Keywords: C32; C51; C52; E21; E41; 330; Johansen procedure; cointegrated VAR; growth rates; cointegration means; linear switching algorithm; consumption; money demand; savings ratio.